The Impact of Work Environment and Job Satisfaction on Employee Loyalty - Wularsih, Endang Ammi`; Octafian, Ray (MultiTech Publisher, 2024)
STIEPARI Semarang is a public organization engaged in educational services. As an education provider, STIEPARI Semarang is truly required to show its professionalism in the form of improvements and enhancements in organizational performance. STIEPARI Semarang's main task is to produce the best graduates according to stakeholders' needs. Seeing this, STIEPARI Semarang must strive as much as possible to improve its performance quality to compete and become a leading higher education institution in management and tourism in line with its vision and mission. Some employees also arrived late and took breaks exceeding the stipulated time. In this research, the type of study used is explanatory research or explanatory level research. Based on the type of explanatory research, this research is classified as associative research. The sampling technique used in this research is census sampling, where the entire population, which is 89 employees The work environment has a positive impact on employee loyalty. As a result, more employee loyalty to the company is strongly correlated with a happy and encouraging work environment. Job satisfaction has a big impact on employee loyalty. As a result, there exists a strong association between employees' job satisfaction levels and their loyalty to the company